Nick O'Dell: capstone - O'Dell, Nicholas, artist (Colorado State University. Libraries, 2021)
The artist's statement: With an artist and avid painter for a mother and a father with a passion for world travel, becoming an artist might not sound like an unlikely career choice, but art is just one of the many possible career paths I could have followed in life. From an early age, science and space exploration, the nature of human consciousness, and the variety of landscapes and cultures that make up our natural world have all fascinated me. It wasn't until my college studies in psychology and an examination of my own existence and place in this world, that I was led back to the subject of art and realized its vast potential as my chosen professional path in life. When people ask why I became a graphic designer, I usually tell them it is because design is an opportunity to creatively blend all of these diverse subjects. My work is a reflection of these varied interests and my captivation with the natural and man-made visual world that surrounds me. This integration of our collective story as humans, transcribed through visual art, enhanced by today's technology, and building on the influence of the talented artists that came before me, is the aim of my work and what gives it so much possibility for the future. For a long time, I believed that I needed to find my own artistic style to set myself apart from others and establish my own identity as an artist. Yet I've since realized that this artistic flexibility is one of my biggest strengths and my appreciation for such a wide variety of arts from throughout time and across the world is exactly what I bring to the table with my designs. The art that I create draws from my repertoire of diverse influences and work experience and will continue to explore any mediums and methods at my disposal. Whether through the use of typography, illustration, branding materials, or product design, my skill set as a designer will continue to evolve by utilizing both traditional and cutting-edge techniques to expand what is possible with modern design. I strive to create the best design solutions possible, both for myself, the team I work with, and our customers in the community and around the world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design